Properties and Toxicity of Cobalt(II) Complex with 2,4,5-triphenyl-1H-imidazole Ligand - Fahimah Martak; Nuari Wahyu Dwi Cahyani; Zjahra Vianita Nugraheni; Wahyu Prasetyo Utomo (Indonesian Journal of Chemistry, 2016)
Binuclear cobalt(II) complex with 2,4,5-triphenyl-1H-imidazole ligand has been synthesized using reflux method. The yellowish green crystals with needle-like shape were obtained. Determination of molecular formula of the complex was carried out using Atomic Absorption Spectroscopy (AAS) and CHN elemental analysis. The contents of carbon, hydrogen, nitrogen and cobalt(II) in the complex were 36.28, 5.32, 4.17, and 16.64% by weight, respectively. The calculation of element composition showed that the molecular formula of complex [(H2O)5Co-L-Co(H2O)5]Cl3. The IR spectrum showed absorption peaks of Co-N and Co=O at 397.31 and 493.74 cm-1, respectively, confirming the formation of complex. The complex compound showed paramagnetic properties with μeff value of 3.18 BM. Toxicity of the complex was determined by Brine Shrimp Lethality Test (BSLT) method, and the LC50 value of the complex was 362.24 mg/L.